Assessment of the nociceptive response to the use of cannabidiol alone and in combination with meloxicam through infrared pupillometry in female dogs undergoing elective ovariohysterectomy - Casas-Alvarado, Alejandro; Martínez-Burnes, Julio; Hernández-Ávalos, Ismael; Mora-Medina, Patricia; Miranda-Cortés, Agatha; Domínguez-Oliva, Adriana; Mota-Rojas, Daniel (Frontiers in Veterinary Science, 2024)
The negative effects of pain are a constant concern in the surgical management of animals, leading to the search for new drugs or more effective analgesic protocols to control this negative emotion. This study aimed to evaluate the nociceptive response of cannabidiol alone and in combination with meloxicam using infrared pupillometry in female dogs undergoing elective ovariohysterectomy under isoflurane anesthesia. A total of 60 female dogs of different breeds were included. These dogs were randomly assigned to four study groups according to the treatment: Control Group (G0: n=15) receiving saline solution; group premedicated with meloxicam at a dose of 0.2 mg Kg -1 IV (GMelox: n=15). Postoperatively this drug was used at 0.1 mg Kg -1 IV every 24 h; the CBD-treated Group (GCBD: n=15) at a dose of 2 mg Kg -1 orally in the preoperative. Postoperatively was administrated every 12 h; and the Group premedicated with the combination of meloxicam and CBD (GMelox/CBD: n=15) Meloxicam at a dose of 0.2 mg Kg -1 IV preoperatively, and 0.1 mg Kg -1 IV during the postoperative. CBD at a dose of 2 mg Kg -1 orally in the preoperative, and every 12 h in the postoperative. Treatments were administered for 48 postoperative hours. After OVH, the pupillary neurologic index, pupillary size, minimum diameter (MIN), percentage change, constriction latency (Lat), constriction velocity, and maximum constriction velocity were recorded as pupillometric variables in both eyes during events (E): Baseline (30 min before drug administration), E30 min, E1h, E2h, E3h, E4h, E8h, E12h, E24h, and E48h. The Short-Form of the Glasgow Composite Measure Pain Scale (GCMPS-SF) was used to assess pain during the same events. Overall, it was observed that the pupillometric variables Size, MIN., and Lat. were significantly higher in G0 compared to the other groups during E30 min, E1h, and E2h (P=0.03), indicating greater pupil dilation in G0 animals. Additionally, no statistically significant differences were observed in GCMPS-SF between GMelox, GCBD, and GMelox/CBD during the postoperative period (P>0.05). In contrast, the scores were statistically different compared to G0, where all animals in this group received rescue analgesia at 2 h post-surgery.